RESEARCH ON PREVALENCE OF OLIGOHYDRAMNIOS IN THIRD TRIMESTER OF PREGNANCY AND ITS OUTCOME: Pharmaceutical Science-Pharmacy Practice - SATHYAPRIYA K; SONAL ANTO; VENKATESWARAMURTHY N; SAMBATHKUMAR R (International Journal of Life Science and Pharma Research, 2019)
The aim of the study is to find out the prevalence of oligohydromnios in third trimester of pregnancy and its outcome. The main objective is to study the risk factors, complications associated with oligohydramnios and its impact on fetal outcome. A prospective observational study was carried out in obstetrics and gynecology hospital in Erode, Tamil Nadu. 100 patients with gestational age from 30-40 weeks with Amniotic Fluid index AFI<5cms with intact membranes were analysed for perinatal outcome during the period April 2018 to September 2018. Out of 100 patients, 25 patients were reported to be with oligohydramnios. More patients were reported in the age group of 21-25years. 80% of patients showed primigravida and 20% of patients showed multigravida. 64% of people showed gestational period of 35-37weeks. All patients showed AFI ≤25%. The frequency of different risk factors in pregnancy included gestational diabetes mellitus (GDM) (24%), anemia (16%), premature rupture (12%), preeclampsia (12%) and with non-maternal factors (36%). Lower Segment caesarian Section (LSCS) was done in 96% of patients and 4% of patients undergone normal vaginal delivery. The LSCS was highly indicated due to oligohydromnios in 48% of cases and its associated causes such as fetal distress 32%, intrauterine growth retardation 12%, malformation 4%and failed induction 4%. All 25 babies of oligohydramnios patient showed Appearance, Pulse, Grimace, Activity, and Respiration (APGAR) score of above ≥7 and associated fetal outcomes such as Respiratory Distress Syndrome 32%, and Preterm 12%. The patients in primigravida are more prone to oligohydramnios with associated factors such as GDM and anemia. In the third trimester, the complications resulting in the caesarian section was high in order to improve the fetal outcome. So timely screening for Amniotic fluid index (AFI) between intrapartum and postpartum pregnancy, proper antenatal checkup and lifestyle changes in patients helps to reduce the maternal risk factors and improve the fetal outcome.